KREASI MASAKAN ORANG MELAYU - Nadilla Resti Amanda; Yasnel Yasnel (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This article aims to explore Malay culinary creations, with a focus on innovation and preservation of culinary traditions in the Kampar area. Using a qualitative approach, this research collects and analyzes literature related to Malay cuisine and involves focused discussions to provide in-depth context. The research results show that Malay cuisine not only represents cultural heritage, but also undergoes transformation through the use of local ingredients, integration with international cuisine, and creativity in presentation. This innovation is important to attract the attention of the younger generation and ensure that Malay cuisine remains relevant in the era of globalization. The conclusions of this research emphasize the need to balance innovation and preservation of tradition, as well as the importance of culinary education to introduce traditional recipes and techniques to the next generation, so that Malay cuisine can continue to develop without losing its cultural roots.